Martabat Manusia di Era Digital: Relevansi Redemptor Hominis di Tengah Perubahan Sosial (International Forum of Researchers and Lecturers, 2024)
The digital age has brought significant changes to human life, from the way we communicate to work patterns and access to information. However, these technological advances also pose major challenges to human dignity, including the threat of dehumanization, exploitation of personal data, and unequal access to technology. This article uses a qualitative method with a descriptive-analytical approach through literature review and case study analysis. The article finds that the digital age has an ambivalent impact: on the one hand, it presents opportunities such as wider access to information, economic empowerment, and strengthening intercultural dialogue; on the other hand, it also exacerbates dehumanization, privacy violations, and the digital divide. Through the Redemptor Hominis framework, this article asserts the importance of placing human beings at the center of technological innovation, with the principles of solidarity and justice as ethical foundations.